Flash Fiction from North Africa - Yasmina Saleh; Mahmoud Kandeel; Hassan Bekkali; Ali Lateef; Brahim Dargouthi; Essam M. Al- Jassim ([sic])
Yasmina Saleh – Algeria At least five or six of them, maybe even more, had overrun his house and family. He was not a politician, an inciter of dissent, nor a troublesome writer; he was a decent citizen. Yet they permeated his little dreams and reluctant joys. The darkness and gloominess of the Algerian night increased after the first shot was fired; the family was overcome with unspeakable dread. Another scene of horrible confusion, terror, and carnage ensued.Mahmoud Kandeel – Egypt Despite the tombstones surrounding her, the place felt empty. The cemetery stood still but for her nervous figure, sitting and fidgeting beside a green, rusted dumpster. Agitated, the woman stuck her right hand inside her blouse and fiddled with something unseen, as though desperately searching for something lost.“Look, she’s caressing her breasts,” my companion whispered with a snicker.